The Hunters : To Hell and Gone - Book 1 - West, Charles (Thorndike, Maine : Center Point Large Print, 2024)
"Orphaned in a massacre. Raised by Crow Indians. Destined to become a powerful hunter, a legendary scout, and a true American hero . . . As a widower with three young boys, Duncan Hunter dreamed of a new life for his sons in the heart of Washington Territory. But the journey was doomed from the start. Before reaching Hell Gate, their wagon train was attacked by Blackfoot Indians. Most of the pioneers were viciously murdered. But Hunters son Cody survived -- taken in by Crow Indians and raised as one of their own. They called the boy Crazy Wolf. This is his story . . . From hunting and tracking on the American frontier to leading patrols on covert missions for the U.S. Army, Cody Hunter would become one of the most valued scouts in the nation. But a part of him would always be Crazy Wolf -- a man of two worlds, as wild and free as the land itself. And every bit as dangerous . . ."--
Keywords: Indian captivities -- Fiction; Scouting (Reconnaissance) -- Fiction; Crow Indians -- Fiction; Frontier and pioneer life -- Fiction; Yellowstone River Valley -- Fiction; Western fiction; Historical fiction; Large print books